2018
DOI: 10.1037/ser0000171
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in associations between DSM–5 posttraumatic stress disorder symptom clusters and functional impairment in war veterans.

Abstract: Understanding the links between posttraumatic stress disorder (PTSD) symptoms and functional impairment is essential for assisting veterans in transitioning to civilian life. Moreover, there may be differences between men and women in the relationships between PTSD symptoms and functional impairment. However, no prior studies have examined the links between functional impairment and the revised symptom clusters as defined in the Diagnostic and Statistical Manual of Mental Disorders, 5th ed. (DSM-5; American Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…While gender emerged as a signi cant predictor in the overall hierarchical regression, implicating higher psychological distress among the female PTSD group, no signi cant difference was observed when psychological distress scores were compared between PTSD males and females, a nding contrary to those noted in the general population whereby women typically have signi cantly higher levels [e.g., 39]. Despite the fact that gender comparisons for social support in the PTSD sample yielded little in terms of signi cant differences, PTSD women did report signi cantly higher levels attachment, a nding consistent with the Meyer et al (2018) study suggesting that functional impairment for men may re ect distancing from others [29]. In terms of the potential social support-PTSD causal relationship, this may raise an interesting question as to whether social erosion may be more likely among male PTSD sufferers, and hence an important topic for future studies.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…While gender emerged as a signi cant predictor in the overall hierarchical regression, implicating higher psychological distress among the female PTSD group, no signi cant difference was observed when psychological distress scores were compared between PTSD males and females, a nding contrary to those noted in the general population whereby women typically have signi cantly higher levels [e.g., 39]. Despite the fact that gender comparisons for social support in the PTSD sample yielded little in terms of signi cant differences, PTSD women did report signi cantly higher levels attachment, a nding consistent with the Meyer et al (2018) study suggesting that functional impairment for men may re ect distancing from others [29]. In terms of the potential social support-PTSD causal relationship, this may raise an interesting question as to whether social erosion may be more likely among male PTSD sufferers, and hence an important topic for future studies.…”
Section: Discussionsupporting
confidence: 64%
“…For instance, based on the DSM-5 PTSD diagnostic criteria, Murphy, Elklit, Chen, Ghazali, and Shevlin (2018) reported that women scored higher on emotional cue reactivity while men tended to report more self-destructive behaviours [28]. Similarly, Meyer, Konecky, Kimbrel, DeBeer, Marx, Schumm et al (2018) observed that functional impairment for men may be more re ective of distorted negative perceptions and distancing from others, while women's functional impairment may be primarily in uenced by rage, over-alertness, carelessness, and insomnia [29].…”
Section: Ptsd Gender Differences and Social Supportmentioning
confidence: 99%
“…Post-Traumatic Stress Disorder is a sexually dimorphic condition such that women are affected with PTSD at twice the rate of men (Kessler et al, 1995;Haskell et al, 2010;Christiansen and Elklit, 2012;Charak et al, 2014;Gamwell et al, 2015;Garza and Jovanovic, 2017;Meyer et al, 2018). While female sex remains a risk factor, the sexual dimorphism present in the acquisition (Inslicht et al, 2013), presentation (Olff et al, 2007;Hourani et al, 2015), and treatment efficacy (Blain et al, 2010) of PTSD suggests that there are underlying biological differences based on sex that need to be investigated separately in both sexes (Cahill, 2003a(Cahill, ,b, 2006Pineles et al, 2017).…”
Section: Developing a Female Animal Model To Study Susceptibility Facmentioning
confidence: 99%
“…Additionally, one study found sex differences among SM/Vs experience of PTSD symptoms, such that female SM/Vs experienced hyperarousal symptoms as the most functionally impairing symptom of PTSD, whereas male SM/Vs reported the greatest functional impairment with negative alterations in cognition/mood (Meyer et al, 2018). Another study observed that while males had increased risk for a PTSD diagnosis relative to females, exposure to MST significantly increased risk for PTSD in females relative to males (Tannahill et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, researchers might consider the role of stressors that are unique to these underrepresented groups, such as the impact of racial discrimination on PTSD symptoms and relationship outcomes among minority SM/Vs in couple‐based therapy (Carlson, Endlsey, Motley, Shawahin, & Williams, ). Additionally, one study found sex differences among SM/Vs experience of PTSD symptoms, such that female SM/Vs experienced hyperarousal symptoms as the most functionally impairing symptom of PTSD, whereas male SM/Vs reported the greatest functional impairment with negative alterations in cognition/mood (Meyer et al, ). Another study observed that while males had increased risk for a PTSD diagnosis relative to females, exposure to MST significantly increased risk for PTSD in females relative to males (Tannahill et al, ).…”
Section: Discussionmentioning
confidence: 99%